Antimicrobial resistance monitoring in commensal enterococci from healthy cattle, pigs and chickens across Europe during 2004–14 (EASSA Study). (8th January 2019) - de Jong, Anno; Simjee, Shabbir; Rose, Markus; Moyaert, Hilde; El Garch, Farid; Youala, Myriam; ,
Abstract: Objectives: The European Antimicrobial Susceptibility Surveillance in Animals (EASSA) programme collects zoonotic and commensal bacteria from healthy food-producing animals at slaughter and tracks their susceptibility to medically important antibiotics. Results for enterococci, collected over three time periods, are presented. Methods: Intestinal contents from cattle, pigs and chickens were randomly sampled (five or six countries/host; at least four abattoirs/country; one sample/animal/farm) for isolation of enterococci; antimicrobial susceptibilities were centrally assessed by CLSI agar dilution. Clinical breakpoints (CLSI) and epidemiological cut-off values (EUCAST) were applied for data interpretation. Results: In total, 2435 Enterococcus faecium and 1389 Enterococcus faecalis strains were recovered. Seven E. faecium/faecalis strains were linezolid resistant. One E. faecium strain was non-WT (NWT), with a daptomycin MIC of 8 mg/L. Clinical vancomycin resistance was very low or absent; eight strains had decreased susceptibility (MICs of 8 mg/L). Two strains were clinically resistant to tigecycline. Little resistance to ampicillin or gentamicin was observed. Clinical resistance of E. faecium to quinupristin/dalfopristin was slightly higher (2.2%–33.6%) and 38.5%–83.2% of the strains were classified NWT. Very high resistance to tetracycline (67.4%–79.1%) and erythromycin (27.1%–57.0%) was noted for E. faecium and E. faecalis in pigs and chickens. For both of these compounds, similar NWT results were observed for Enterococcus hirae ( n  = 935), Enterococcus durans ( n  = 286) and Enterococcus casseliflavus ( n  = 154) whereas the percentage of NWT for linezolid, tigecycline and vancomycin was generally zero or low. Conclusions: In this pan-EU survey of commensal enterococci, antibiotic susceptibility varied widely between antibiotics, animal species, countries and enterococcal species. Clinical resistance to antibiotics that are critically important for human medicine was absent or low, except for erythromycin.